A perspectiva dos esprits animaux como causa dos movimentos corporais e das paixões em Descartes - Nogueira, Abraão Carvalho (2017)
In the reading of the Cartesian works Treatise of Man (1648) and The Passions of Soul (1649), we find a essential category for comprehension to cartesian dualism: the concept of animal spirits. This concept articulates one of the main foundations of the comprehension of the french philosopher René Descartes (1596-1650) in relation to body and soul dualism. The component physical and corporeal of this relation between the body and soul for Descartes, in this perspective, resides mainly in the movement and action of the animal spirits in the body, which are produced through the brain, as shown in Art. X of The Passions of Soul in the part named How animal spirits are produced from the brain. Essential for understanding of this concept and your teoric formulation is ambiented through by other conception: body machine, as formulations in reference to philosophical materialism. Animal spirits and body machine are two essential concepts for de comprenhension of the philosophical interlocution between Descartes and La Mettrie (1709-1751) in the work's The Man Machine (1895) and Animals More than Machines (1796). Causality and mechanical movements of the bodies are conceptions that expression approximation and confront between this two philosophers.